Early Warning and Management Measures for the Non-Agriculturalization of Cultivated Land in Shaanxi Province of China Based on a Patch-Generated Land Use Simulation Model - Huiting Yan; Hao Chen; Fei Wang; Linjing Qiu; Rui Li (Agriculture)
This study aimed to analyze the spatiotemporal trends of the non-agriculturalization of cultivated land (NACL) and evaluate the effectiveness of land management strategies in Shaanxi Province, China. First, geostatistical analysis was conducted to examine NACL dynamics, revealing that most areas remained in a mild early warning state from 2000 to 2010. However, warning levels escalated to severe or extreme in northern Shaanxi, parts of Guanzhong, and southern Shaanxi between 2010 and 2020. Subsequently, the Patch-Generated Land Use Simulation Model (PLUS) was employed to simulate NACL under different land management scenarios, using 2020 as the baseline and 2035 as the target year. The scenarios include natural growth (NG), cultivated land protection (CP), and ecological protection (EP), which were designed based on national and provincial land use planning objectives for 2035. The results indicated that, under the NG scenario, the overall NACL area is projected to decline by 2035, although northern and southern Shaanxi will remain highly susceptible to NACL. The CP scenario effectively mitigated NACL, reducing warning levels to moderate or mild in parts of Guanzhong and northern Shaanxi. Spatial clustering analysis further revealed that NACL in northern Shaanxi consistently exhibited high–high clustering in both historical periods and across different management scenarios. These findings establish a research framework for identifying and forecasting NACL while providing a scientific basis for optimizing land resource allocation and informing policy decisions.